Environment in the conception of users of the São João river and Tocantins river in Porto Nacional city/TO - Carvalho, Aurean de Paula; Paula, Maria Anunciada Nery Rodrigues de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The present study it had as objective to evaluate the level of knowledge of bathers and fishermen users São João River and Tocantins River in the city of Porto Nacional, TO, on environmental issues, as well as producing knowledge that will subsidize the Government in planning environmental awareness campaigns. To this end, data collection were used questionnaires with closed and open questions. The analyzed data revealed that respondents have environmental conception, confused, fragmented, revealing deficiency in environmental perception. The variable was deficient environmental vision and the evaluated better variable the environmental responsibility.